METHODOLOGICAL APPROACHES TO DEVELOPMENT REGIONAL INTERACTION CENTER «GOVERNMENT-BUSINESS-SCIENCE» IN THE CONTEXT OF «TRIPLE HELIX» MODEL - V. Mikhaylov (Вестник университета, 2016)
The article describes the interaction mechanisms of external forms and methods of partnership of science/education, business and government in the context of «triple helix» model. The author suggests a project to development regional research and education interaction center «government-business-science».